2009
DOI: 10.1523/jneurosci.3239-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glial Cell Line-Derived Neurotrophic Factor (GDNF)–Neural Cell Adhesion Molecule (NCAM) Interactions in Induction of Neurite Outgrowth and Identification of a Binding Site for NCAM in the Heel Region of GDNF

Abstract: The formation of appropriate neuronal circuits is an essential part of nervous system development and relies heavily on the outgrowth of axons and dendrites and their guidance to their respective targets. This process is governed by a large array of molecules, including glial cell line-derived neurotrophic factor (GDNF) and the neural cell adhesion molecule (NCAM), the interaction of which induce neurite outgrowth. In the present study the requirements for NCAM-mediated GDNF-induced neurite outgrowth were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 71 publications
2
55
0
1
Order By: Relevance
“…An additional signaling receptor for GFRα1 is NCAM (48), which mediates neurite outgrowth induced by GDNF in cultured hippocampal neurons (49). In the absence of GDNF, GFRα1 binds NCAM, inhibiting cell adhesion mediated by homophilic NCAM interaction.…”
Section: Discussionmentioning
confidence: 99%
“…An additional signaling receptor for GFRα1 is NCAM (48), which mediates neurite outgrowth induced by GDNF in cultured hippocampal neurons (49). In the absence of GDNF, GFRα1 binds NCAM, inhibiting cell adhesion mediated by homophilic NCAM interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, NCAM has been reported as an alternative signaling receptor for GDNF (Charoy et al, 2012;Ledda et al, 2007;Nielsen et al, 2009;Paratcha et al, 2003). Whereas the GDNF tyrosine kinase receptor Ret is not expressed in hippocampal neurons, NCAM is highly expressed in this brain area.…”
Section: Knockdown Of Gfrα1 In Hippocampal Neurons Restricts Postsynamentioning
confidence: 96%
“…Furthermore, both BDNF and GDNF are used in established protocols for the differentiation of human ES cells into dopaminergic neurons in vitro (Perrier et al, 2004;Sonntag et al, 2007;Cooper et al, 2010) and have neuroprotective effects on endogenous neurons in animal models of neurodegenerative diseases (Grondin and Gash, 1998;Zuccato and Cattaneo, 2009). Interestingly, BDNF (Cassens et al 2010) and GDNF (Nielsen et al, 2009) have been shown to be functionally connected to neural cell adhesion molecules and thus, beneficial effects of overexpression of these neurotrophins might be mediated by neural cell adhesion molecules and therefore, overexpression of cell adhesion molecules instead of neurotrophins might prevent potential adverse effects of neurotrophin overexpression such as induction of neuropathic pain (Geng et al, 2010). Similar neuroprotective effects on endogenous host-derived neurons are mediated by the transplantation of neural stem cells into rodent animal models of Parkinson´s disease Yasuhara et al, 2006) or spinal cord injury (Teng et al, 2002), probably due to neuroprotective factors secreted by engrafted cells.…”
Section: The Role Of the Recognition Molecules L1 And Tnr On Endogenomentioning
confidence: 99%